PENERAPAN METODE KANBAN PADA PROSES PACKING DI PERUSAHAAN MAKANAN PT XYZ - Novianti Herdian; Daryana Daryana; M Fadhil; Muchammad Fauzi (Jurnal Taguchi : Jurnal Ilmiah Teknik dan Manajemen Industri, 2021)
The purpose of this research is to assist in controlling the packaging material preparation process to eliminate stop lines in the packing section so that product delivery is fulfilled by applying the Kanban method. PT XYZ is a company engaged in food that has several regular customers and new customers for product marketing. The demand for each customer's product increases so that they experience problems in product fulfillment. Delivery delays in the process of preparing packaging materials are one of the factors supporting the constrained packing process. The application of the kanban system in the packing production process causes the packaging material delivery system to be properly scheduled and controlled so that the packaging material will be available in the production process area at the required time so as to minimize the occurrence of line stops.